1996
DOI: 10.1144/gsl.sp.1996.117.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Sequence stratigraphy and architecture on a ramp-type continental shelf: the Belgian Palaeogene

Abstract: In Palaeogene times, the 'Southern Bight' of the North Sea functioned as an intracratonic, shallow-marine, siliciclastic basin and accumulated a few hundred metres of gently dipping sediment packages. A fine-scale seismic-stratigraphical model for the Palaeogene was formulated on the basis of a dense, high-resolution reflection seismic grid. In total 13 major seismic-stratigraphical units were defined, based on geometry and seismic facies characteristics. The seismic stratigraphy has been complemented with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In addition, methanogenesis increased in the deep-sea sediments, thus favoring the formation of early diagenetic siderite. Siderite and benthic foraminiferal assemblages similar to those found in the North Iberian continental margin also characterized other continental margins during the early Eocene climatic optimum (Jacobs and De Batist, 1996;Schmitz et al, 1996;Huggett et al, 2000;Racey et al, 2001;Kaminski and Gradstein, 2005;Silver, 2009;King et al, 2013;Deprez et al, 2015;Waskowska, 2015), suggesting that the inferred paleoenvironmental conditions may have extended supraregionally. These processes, together with terrestrial clay dilution, may actually account for the carbonate decrease also found in many other continental margins during the early Eocene climatic optimum (e.g., Slotnick et al, 2012), thus blurring the deepening of the lysocline generally modeled for long-term global warming episodes (Leon-Rodriguez and Dickens, 2010;Sluijs et al, 2013).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, methanogenesis increased in the deep-sea sediments, thus favoring the formation of early diagenetic siderite. Siderite and benthic foraminiferal assemblages similar to those found in the North Iberian continental margin also characterized other continental margins during the early Eocene climatic optimum (Jacobs and De Batist, 1996;Schmitz et al, 1996;Huggett et al, 2000;Racey et al, 2001;Kaminski and Gradstein, 2005;Silver, 2009;King et al, 2013;Deprez et al, 2015;Waskowska, 2015), suggesting that the inferred paleoenvironmental conditions may have extended supraregionally. These processes, together with terrestrial clay dilution, may actually account for the carbonate decrease also found in many other continental margins during the early Eocene climatic optimum (e.g., Slotnick et al, 2012), thus blurring the deepening of the lysocline generally modeled for long-term global warming episodes (Leon-Rodriguez and Dickens, 2010;Sluijs et al, 2013).…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, abundant iron concretions and high organic carbon content, both related to dysoxic conditions, also characterize many coeval (NP12, E5, C23r-C22r) Boreal and Tethyan continental margin deposits (Fig. 6), such as those in Belgium (Kortemark Member of the Ieper Clay Formation in the VR1 well; Jacobs and De Batist, 1996), Denmark (units E and F of the Rosnaes Clay Formation; Schmitz et al, 1996) basins; Silver, 2009;Waskowska, 2015), and Kazakhstan (unit B1 of the Aktulagay section; King et al, 2013;Deprez et al, 2015). This all suggests that methanogenesis may have been a widespread process in continental margin seabed sediments during the early Eocene climatic optimum, but further data from other areas would be required in order to determine whether methanogenesis increased globally (Gu et al, 2011).…”
Section: Core Of the Early Eocene Climatic Optimummentioning
confidence: 99%
“…Lateral accretion of point bars, with upward‐fining cycles (Figure ) indicate floodplain deposits (Miall, ), while pockets with a dominant sandy, clayey or silty facies upstream in the Coastal Valley suggest variable energy conditions within the fluvial environment. The presence of reworked Paleogene material is derived directly from the pre‐Quaternary strata with a marine origin (De Batist, ; Jacobs and De Batist, ) certainly not possibly through erosion. This supports sedimentological and palaeoenvironmental interpretations by Heyse () who interprets a subaquatic origin for this unit (also known as the periglacial Adegem Formation, Table ) that largely comprises reworked marine sands of Paleogene origin.…”
Section: Resultsmentioning
confidence: 99%
“…The pre‐Quaternary surface can be morphologically subdivided into three major planation surfaces (Marginal, Middle and Offshore Platforms), each bound by escarpments or slope breaks that cut across different Paleogene strata of varying resistance (De Batist, ; Liu, ; Mathys, ; De Clercq et al ., ) that were formed under marine to near‐coastal conditions (Gibbard and Lewin, ; Boulvain and Vandenberghe, ). This setting resulted in a lateral changing lithology composed of consolidated clays and sand‐silt‐clay layers locally containing sandstone layers (De Batist, ; Jacobs and De Batist, ; Le Bot et al ., ). Just offshore from the modern shoreline, the Marginal Platform divides into three segments (Western, Central and Eastern Marginal Platform) separated by the palaeo‐Scheldt River (Ostend and Zeebrugge Valleys), while in the western coastal plain the isolated drainage system of the Yser Valley is situated (Bogemans et al ., ).…”
Section: Geomorphological – Stratigraphical Settingmentioning
confidence: 99%
“…The subsurface of this region is characterized by gently NNE-dipping Cenozoic siliciclastic, shallow-marine sediments. They belong to the Southern Bight of the North Sea, known as the Belgian Basin (Jacobs & De Batist 1996). Relative sea-level changes controlled the nature and architecture of these sediments by accumulating alternating clay and sand packages.…”
Section: Geological Setting and Historical Usementioning
confidence: 99%